(untitled) (Mongolian Journal of Chemistry, 2021)
Global warming is expected to affect stream metabolism significantly; and higher temperatures may lead to higher respiration and thus higher risk of oxygen depletion. It is, therefore, crucial to obtain reliable data on the oxygen dynamics in the different stream compartments. Determination of sediment oxygen demand (SOD) is typically based on lab or field measurement using cores or benthic chamber in which the actual physical conditions in the streams are not possible to mimic perfectly. We compared SOD based on lab core incubations with SOD measured in situ in stream sections where the oxygen exchange between water and air was eliminated artificially. The in situ SOD increased with increasing oxygen concentrations and both the temperature and the oxygen dependency of SOD increased with increasing organic content in the surface sediment. The laboratory rates reached 17 - 83% of the rates obtained in situ. The percentages were especially low at low stream velocity, likely reflecting a pure imitation of the physical conditions near the sediment in the lab when the sediment organic content was high (at low velocity). Therefore, alternative methods, simulating the natural horizontal water flow, are needed to provide reliable information on SOD in streams.